Transient rise in CA 125 in a woman with ovarian carcinoma and COVID-19 infection (2020)
Cancer antigen 125 (CA 125) is a transmembrane glycoprotein expressed on the surface of germinal epithelium and other tissues derived from embryonic coelomic epithelium (Bischof, 1993). CA 125 is a useful biomarker to detect treatment response and recurrence of ovarian malignancy (Montagnana et al., 2017), however, its use as a diagnostic marker is precluded by its limited specificity. CA 125 can be elevated in several non-ovarian malignancies including cervical, lung, and colorectal cancers (Johnson et al., 2008), and have also been found to be elevated in benign diseases involving coelomic epithelium, such as endometriosis, fibroids, ovarian cysts, and pelvic inflammatory disease (Sevinc et al., 2007).